ANALISIS KOMPETENSI TENAGA KEPENDIDIKAN DI SEKOLAH MENENGAH ATAS NEGERI 18 GARUT - Ikeu Kania (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
Principals, school administrators, and other personnel deliver quality education. School administration employees are educators that help school administration. This research seeks to evaluate how education staff may improve service quality at SMA Negeri 18 Garut. This study employed qualitative research with descriptive analysis. Based on the study, SMA Negeri 18 Garut's education professionals have three skills to improve service quality in line with the National Education Government Regulation No. Efforts to improve school administration at SMA Negeri 18 Garut include training educational personnel, finger prints at every entry and exit, monthly motivation and morale meetings, and comparison studies with other schools. Provide care for the teaching personnel of SMA Negeri 18 Garut.